Evaluation of blood metabolites in dairy cows grazing under two pasture allowances and supplemented with corn silage under restricted grazing conditions - Morales,Álvaro (2016)
ABSTRACT This study was conducted to evaluate the influence of management tools - daily pasture allowance and corn silage supplementation - during periods of forage shortage on the metabolism of dairy cows grazing low-mass pasture in temperate regions. Forty lactating Holstein cows were used during an experimental period of seventy days (April 15 to June 23, 2012). Blood metabolites and milk production were determined in fall-calving dairy cows grazing under two daily pasture allowances (PA) (moderate, 17 kg vs. high, 25 kg dry matter (DM)) and supplemented with corn silage (CS) (low, 4.5 kg vs. high, 9.0 kg DM). All cows received 3 kg DM of concentrate. Plasma concentrations of β-hydroxybutyrate (BHBA), non-esterified fatty acids (NEFA), and urea were determined using an automated spectrophotometer, and milk production was electronically measured at each milking time during the trial. The experimental design was completely randomized using a 2 × 2 factorial arrangement of treatments. The increase in daily PA decreased plasma concentrations of BHBA (0.91±0.36 vs. 1.12±0.43 mmol L−1), provided an increase in milk yield (23.18±3.26 vs. 21.99±3.37 kg d−1), and did not modify the concentrations of NEFA and urea. The increased CS supplementation increased mildly the plasma concentrations of BHBA (1.07±0.36 vs. 0.96±0.44 mmol L−1) and NEFA (92.77±54.14 vs. 92.77±55.31 µmol L−1), and decreased the concentrations of urea (4.08±1.40 vs. 4.64±1.30 mmol L−1), but did not change milk production. The positive effect of increasing PA was associated with a high herbage intake, while the lack of response to increasing CS supplementation was attributed to a high substitution of pasture intake (0.9 kg DM pasture/kg DM CS). Low corn silage supplementation is recommended.